A Mentoring Model for Developing an Arabic Language Environment (Bi'ah Lughawiyah) to Enhance Vocabulary Mastery in Madrasah Ibtidaiyah - Mohammad Zainal Hamdy; Wiwik Prasetiyo Ningsih; Moh. Mofid (Al-Ridha: Jurnal Pengabdian kepada Masyarakat, 2026)
Limited vocabulary mastery remains a major challenge in Arabic language learning at Islamic elementary schools (Madrasah Ibtidaiyah), as instruction is still largely dominated by memorization and translation with minimal support from a meaningful Arabic language environment. Consequently, students often struggle to retain and use vocabulary in simple communicative contexts. This study aimed to describe the mentoring process for establishing an Arabic language environment (bi'ah lughawiyah) and to analyze its implementation in improving students' vocabulary mastery at MI Miftahul Ulum Angsokah Timur. The study employed a qualitative case study approach. Data were collected through participatory observation, in-depth interviews, and documentation, and analyzed using the interactive model of Miles and Huberman. The findings revealed that the systematic implementation of bi'ah lughawiyah through daily language habituation, song-based vocabulary memorization, the use of the Green Dictionary (Kamus Hijau), hiwar practice, audiovisual media, and Arabic wall magazines successfully created a language-rich environment that enhanced students' vocabulary mastery, pronunciation accuracy, learning motivation, and self-confidence. This study contributes a contextual mentoring model that integrates classroom instruction with the linguistic culture of the madrasah, offering an effective and sustainable approach to strengthening Arabic language learning at the Islamic elementary school level